Food insecurity increases the risk of overweight and chronic diseases in adolescents: a systematic review and meta-analysis - Chong Zhou; Hongrui Miao; Yingjun Zhao; Xiaohong Wan (Food Science and Human Wellness)
To investigate the relationship between food insecurity (FI) and overweight/obesity (OW/OB) or corresponding chronic diseases in adolescents, 33 studies with 181 135 individuals were included in this meta-analysis. Six studies and 10 studies, reported a higher risk of overweight and obesity in adolescents experiencing FI, respectively (OR 1.38, 95 % CI 1.201.58, P < 0.0001; OR 1.11, 95 % CI 1.011.22, P = 0.035, respectively). Based on the pooled results, adolescents with severe FI had the highest risk of OW/OB (OR 1.45, 95 % CI 1.201.75, P < 0.000 1). The pooled OR indicated no significant association between FI and OW/OB, when the adolescents were stratified into those under 6 years old and those between 6 and 18 years old. Eleven studies assessed the relationship between FI and the risk of chronic diseases. The anemia subgroup was significantly associated with FI (OR 1.67, 95 % CI 1.302.13, P < 0.0001). Severe FI was reported to increase the risk of hypertension (OR 1.59, 95 % CI 1.281.98, P < 0.000 1). Furthermore, a pooled analysis revealed a significant association between FI and the risk of chronic diseases in both 6 and 6−18-year-old subgroups.